EXAMINATION OF FLUENCING FACTORS BY FINDING A JOB FOR MOTHERS WITH LITTLE CHILDREN IN HUNGARY - Vig Salma, Stella; dr.Kőműves, Zsolt (Poslovna ekonomija, 2020)
ABSTRACT: For women with young children, work and parenting are not mutually exclusive, but both are key. Together, the two help them live a full life. At the same time, they can still face a lot of job disadvantages, and those who manage to reconcile the two can be privileged. Based on the literature and its further reflection, we list the factors hindering the employment chances of women with small children. Key words: motivation, state aid, education, equal opportunities.